Utilization of antibiotics in primary healthcare setting / Shafinaz Shamsuddin - Shamsuddin, Shafinaz (2015)
Background : In the primary settings, oral antimicrobial drugs feature consistently in the top leading therapeutic classes of drugs, in terms of frequency of use and cost. This trend is similar in the managed care environment. It is thus imperative to monitor the trend of usage patterns to determine its impact on the managed health care system. Nowadays awareness of the rational use of medicine is increasing among healthcare professionals. The fundamental step on supporting the rational use of medicine is by collecting information on patterns of drug prescriptions and on factors influencing prescribing decisions Objective : To describe the pattern of use of selected antibiotic prescribing for acute infectious diseases among adult in the primary care settings of PKD Klang. Method : This was a retrospective study of the utilization of selected antibiotics in three (3) government health clinics under in Selangor. The Information identified from electronic Clinic Management System (e-CMS) from January to December 2013. The prescribed medicine, frequency and dose were recorded for each patient to obtain the drugs' Defined Daily Dose (DDD) per 1,000 inhabitants per day. We referred Malaysian CPG on the National Antibiotic Guideline 2008 to evaluate the quality of prescribing. Result : A total of 73 5 patient encounters was analysed, females were significantly higher as compared to males (60.4% versus 39.6% %2= 8.8,p = 0.01). Patients aged between 18 to 30 years old was the highest (n=304, 41.4%). However, age range between patients were similar (%2= 3.5, p = 0.48). The mean age (SD) was 36.11 (12.66).From the expenditure data in 2011-2013, Amoxycillin 250mg cap showed the highest purchased and usage item. Total antibiotics used for the 3 clinics is 2.675 DID. The five most utilized antibiotics was Amoxycillin (1.36 DID) followed by Cloxacillin (0.68 DID), Erythromycin (0.32 DID), Cephalexin (0.11 DID) and Bacampicillin (0.13 DID). The Pandamaran health clinic showed the highest utilized Amoxycillin which is (1.49 DID). There was no significant difference between gender and age range. Indian patient consumed the most Amoxycillin 250mg cap (35.8%) followed by Malay (34.8%) and Chinese (33.1%). Amoxycillin 250mg cap is mainly prescribed for respiratory infections (54.2%).